A Study of Digital Ethics and the Application of AI in Arabic Language Learning at MIN 2 Kota Malang - El Hasany, Ikke Nilova; Hasan, Ahmad Makki (Proceeding of International Conference on Islamic Education (ICIED), 2024)
This study investigates the ethical dimensions and practical integration of Artificial Intelligence (AI) in Arabic language learning at the elementary school level, focusing on Grade 5 students at MIN 2 Kota Malang, Indonesia. Employing a qualitative case study design, data were gathered through classroom observations, interviews with Arabic teachers, and an analysis of AI-generated learning materials. Findings reveal that AI-supported tools -particularly Canva AI, AI-based coding games, Quizizz, and Wordwall- are widely used to enhance instructional media, classroom engagement, and assessment efficiency. Canva AI emerged as the most frequently utilized platform due to its rapid and visually appealing content generation. However, several ethical challenges were identified, including students' misuse of AI to complete assessments, inaccuracies in AI-generated Arabic texts, insufficient teacher filtering of AI outputs, and unequal digital competencies among students. These issues highlight gaps in digital ethics implementation, particularly concerning accuracy, transparency, responsible use, and alignment with curriculum standards. Guided by UNESCO's AI Ethics Framework, this study emphasizes the need for stronger teacher digital literacy, clear school-level AI policies, and systematic validation of AI-generated Arabic materials. The research contributes to the limited body of empirical studies on AI use in Arabic language education at the elementary level and provides recommendations for policy, pedagogical practice, and future research to ensure safe, ethical, and effective AI integration in primary education.